MODEL GRAMATIKA KOMUNIKATIF BIMBINGAN SKRIPSI MAHASISWA PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM STAIN SULTAN ABDURRAHMAN KEPULAUAN RIAU - Eka Rihan K (PERADA, 2019)
The communicative grammatical model is one of the models for viewing language competencies involving communication problems in terms of pragmatic, semantic and syntactic components. This communicative grammatical model was chosen to describe the process of student thesis guidance as to what can be communicative walking seen from the components of pragmatics, semantics and syntax. Qualitative descriptive research method. Data collection uses video or audio recording techniques when the thesis guidance process takes place. Besides that, it also uses observation guidelines and interview guide methods while data analysis uses data reduction, data presentation and conclusion / verification. The actual context has alternative units. Some of them are normal and fulfill the basic postulates of the Pragmatic Component communication process Data 19 and Data 31, there are actual context utterances using traits there and from there showing places where the same activities of the speaker and listener are performed. Some utterances in the thesis guidance process between students and supervisors have been found to have been communicative and some have not been communicative on pragmatic components, semantic components and syntactic components. Some command sentence utterances and request sentences on syntactic components have fulfilled various Indonesian sentences from the communicative point of view.